EFEKTIVITAS KOMBINASI VAKSIN BAKTERI POLIVALEN DENGAN VAKSIN ANTI GROUPER SLEEPY DISEASE IRIDOVIRUS (GSDIV) PADA IKAN KERAPU MACAN (Epinephelus fuscoguttatus) - Zafran Zafran (BERITA BIOLOGI, 2016)
One problem in mariculture is mortality caused by diseases. An experiment to evaluate the effectiveness of polyvalent bacterial vaccine combined with anti GSDIV vaccine was conducted in the Institute for Mariculture Research and Development, Gondol, Bali. Polyvalent bacterial vaccine was combined of three inactivated pathogens, i.e. Vibrio harveyi, V. alginolyticus, and Photobacterium leioghnathi. Polyvalent bacterial vaccine administered through bathing method whereas GSDIV vaccine given through intra-peritoneal injection on tiger grouper. The fish was reared for three months in concrete tanks equipped with filter and aeration systems. The fish were fed with dry pellet twice a day. The results showed that titer antibody and survival rate of vaccinated fish were higher than unvaccinated one. The highest titer antibody was obtained on fish vaccinated with GSDIV vaccine (128) followed by fish vaccinated with polyvalent bacterial vaccine (32-64) and combination of polyvalent bacterial vaccine with GSDIV vaccine (32-64), respectively. Relative Percentage Survival (RPS) of vaccinated fish following challenge with live bacteria and virus were ranged from 65-84%. It is suggested that vaccines effective to enhance immune protection of tiger grouper fish against bacterial and viral infections.